Predictors of Mortality of COVID-19 cases In Benazir Bhutto Hospital Rawalpindi - Sidra Tahir , Sadaf Zaman , Lubna Meraj , Faisal Sheraz , Savida Ilyas Dar ,Nadia Shams (Journal of Rawalpindi Medical College, 2021)
Background: There has been a global epidemic of COVID-19 caused by novel corona virus (SARS-2). Current research aims to study the demographic, clinical characteristics and co-morbidities in COVID-19 related deaths. Methodology: This observational (descriptive) study was conducted at BBH Rawalpindi based on data from 1st March-15th June 2020 after ethical approval. Inclusion criteria was the deceased COVID PCR positive cases (>18 years age) of both the genders. Exclusion criteria was negative PCR, doubtful diagnosis and expiry outside the hospital setting. Data was collected from hospital record and family members. Demographic details, symptoms, duration of hospital stay, co-morbidities, type of ventilatory support were documented. Data analysed by SPSS, significant p<0.05. Results: There were 54 expiries from1st March to 13th June, 42(78%) males & 12(22%) females. Mean age was 54.24+12.78 years. 76% had various comorbidities, i.e., diabetes (57%), hypertension (54%), ischemic heart disease (20%); stroke, cancer, COPD and hypothyroidism (<10% each). Most frequent cause of death was acute respiratory distress syndrome due to Covid-19. Two patients died of sepsis and multiorgan failure. 64% of patients received mechanical ventilation and 35% oxygen via non-rebreather mask. There was average 4 days on invasive mechanical ventilator. 51-60 years had longest duration of illness and hospitalization till death, while 20-30 years had the shortest. The average mortality climbed up (25% to 57%) from April to May 2020. Conclusion: COVID-19 claims significant mortality. The risk factors for mortality being age above 50 years, male gender, co-morbidities like diabetes, hypertension, ischemic heart disease, need for mechanical ventilation upon admission and longer duration of illness. There is need to intensify the vaccination and prevention in the community keeping in mind these high-risk groups. The high-risk cases, need to be aggressively managed to reduced mortality and improve outcome.